2011
DOI: 10.5424/fs/20112003-11083
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground soil C inputs in the ecotone between Scots pine

Abstract: Aboveground litterfall from Pyrenean oak (Quercus pyrenaica Willd. a semi-deciduous species), mixed Pyrenean oak-pine and pine (Pinus sylvestris L.) forest stands was surveyed in two sites in a Mediterranean mountain area during a period of 36 and 29 months, respectively. Separation in different litterfall fractions was performed, and C content of each fraction was measured to calculate the C flux to the soil due to litterfall. Our results showed that litterfall input was higher in pine stands than in Pyrenean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(59 reference statements)
2
6
0
Order By: Relevance
“…Confirming our hypothesis, annual R H was highest in the pine stand, where litterfall rates (Diaz-Pines et al, 2011a) and C stored in the topsoil (Diaz-Pines et al, 2011b) are significantly higher than in the oak stand. However, the C turnover rate in soils under pines was roughly twice that of oaks, reflecting the functional traits of leaves and needles Table 5 Seasonal and annual total soil respiration (R s ) and its components (R A : autotrophic, R H : heterotrophic) estimated for each tree species (mean ± SD, n = 3) and given as g C0 2 -C m~ 2 .…”
Section: Soi C Stocks and Cyclingsupporting
confidence: 84%
See 1 more Smart Citation
“…Confirming our hypothesis, annual R H was highest in the pine stand, where litterfall rates (Diaz-Pines et al, 2011a) and C stored in the topsoil (Diaz-Pines et al, 2011b) are significantly higher than in the oak stand. However, the C turnover rate in soils under pines was roughly twice that of oaks, reflecting the functional traits of leaves and needles Table 5 Seasonal and annual total soil respiration (R s ) and its components (R A : autotrophic, R H : heterotrophic) estimated for each tree species (mean ± SD, n = 3) and given as g C0 2 -C m~ 2 .…”
Section: Soi C Stocks and Cyclingsupporting
confidence: 84%
“…transpiration (Poyatos et al, 2005), low growth rates (Camarero et al, 2010;Sabate et al, 2002;Vayreda et al, 2012) and needle fall period from May to September (Diaz-Pines et al, 2011a). The abundant precipitation in the first half of the year may delay the time at which drought stress becomes critical in the pine growing season.…”
Section: Seasonal Patterns Of Soil Respiration Components Modulated Bmentioning
confidence: 99%
“…Martin et al (1996) found that the inter-annual variability of litterfall amount in Q. rotundifolia stand was caused by water stress in summer. Dry spring weather was the reason for the lower amount of litterfall also in Q. pyrenaica stand in Spain (Diaz-Pines et al 2011). Finally, precipitation and water availability as a probable cause of differences in litter production were mentioned by Andivia et al (2013) in stands of Q. ilex.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this interest, a wide range of studies have been published in the last few decades. These studies have included the following aspects (amongst others): development of site index curves, in León (Torre 1994), La Rioja (Bengoa 2000), Castilla y León (Adame et al 2006) and Galicia (Díaz-Maroto et al 2010); fitting height-diameter models (Adame et al 2008); modeling mortality (Adame et al 2010); stand yield in terms of biomass (Allué & San Miguel 1991, Carvalho 2005; and estimation of carbon stocks in Pyrenean oak stands, both in soils (Díaz-Pines et al 2011) and in wood (Castaño-Santamaría & Bravo 2012). However, only one stand-level model has been developed to date and this refers to the province of Leon (Bravo et al 2011).…”
Section: Introductionmentioning
confidence: 99%